(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The present article aims to identify what are the affirmative policies for the inclusion of persons with disabilities in the labour market in Brazil and in Mexico, under the Convention on the Rights of Persons with Disabilities (“CRPD”), which both countries ratified; what are the points of convergence and divergence between their models of affirmative policy, respectively, the establishment of a minimum quota of job vacancies destined to persons with disabilities, and tax incentives to employers who employ persons with disabilities; and what are the challenges these countries face regarding the public policies that were analyzed. The methodology used consists of a bibliographic review.